1990
DOI: 10.1111/j.1365-2621.1990.tb06775.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dough Materials on Flavor Formation in Baked Cookies

Abstract: The effects of dough materials on flavor formation in baked cookies were investigated in detail. The baked cookies were prepared from wheat flour, eggs, butter, sugar and sodium bicarbonate and heated at 150°C for 10 min. This dough was extracted with methanol/water (3:l,v/v) and the extracts were submitted to HPLC. The two main peaks, among 10 peaks detected, were identified as 2,3-dihydro-3,5-dihydroxy-6-methyl-4H-pyran-4-one (DDMP) and 5hydroxymethyI-furfural (HMF), respectively. DDMP seemed to be a key sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 16 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Several studies have confirmed the possibility of producing baked products from 10% cassava-wheat composite flour with tremendous success recorded in their physical, sensory and proximate composition [9].…”
Section: Introductionmentioning
confidence: 93%
“…Several studies have confirmed the possibility of producing baked products from 10% cassava-wheat composite flour with tremendous success recorded in their physical, sensory and proximate composition [9].…”
Section: Introductionmentioning
confidence: 93%
“…The cookie dough was prepared according to the following formula: 100 g flour (containing varying proportion of water chestnut flour and wheat flour) 40 g sugar, 50 g shortening, 1 g sodium chloride, 0.5 g ammonium bicarbonate and sufficient water to make required consistency of cookie dough. Cookie dough was prepared according to the formula of Nishibori and Kawakishi (1990) with slight modifications. The flour containing various proportions of water chestnut and wheat flour, which had been sieved twice, was mixed with shortening and rubbed in till uniform.…”
Section: Pasting Propertiesmentioning
confidence: 99%
“…Cookies were prepared according to the formula of Nishibori & Kawakishi (1990), with slight modifications. Sucrose and margarine were used in place of glucose and butter in the original formula (Akpapunam & Darbe, 1994).…”
Section: Preparation Of Cookiesmentioning
confidence: 99%